2013
DOI: 10.1007/s00216-013-7467-z
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in dispersive liquid–liquid microextraction

Abstract: During the past 7 years and since the introduction of dispersive liquid-liquid microextraction (DLLME), the method has gained widespread acceptance as a simple, fast, and miniaturized sample preparation technique. Owing to its simplicity of operation, rapidity, low cost, high recovery, and low consumption of organic solvents and reagents, it has been applied for determination of a vast variety of organic and inorganic compounds in different matrices. This review summarizes the DLLME principles, historical deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
90
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(95 citation statements)
references
References 235 publications
1
90
0
4
Order By: Relevance
“…Moreover, the dispersive solvent allows for the extracting solvent to partition itself uniformly in the water sample and thus to achieve effective and rapid mass transfer. To accomplish this usually relatively large volumes of dispersive solvents are required (in the order of several milliliters), which decreases the partition coefficient of analytes into the extraction solvent [37][38][39]. This problem can be avoided by using ultrasonic stirring or a cationic surfactant in order to disperse the extraction solvent instead of dispersive solvent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the dispersive solvent allows for the extracting solvent to partition itself uniformly in the water sample and thus to achieve effective and rapid mass transfer. To accomplish this usually relatively large volumes of dispersive solvents are required (in the order of several milliliters), which decreases the partition coefficient of analytes into the extraction solvent [37][38][39]. This problem can be avoided by using ultrasonic stirring or a cationic surfactant in order to disperse the extraction solvent instead of dispersive solvent.…”
Section: Introductionmentioning
confidence: 99%
“…All of them ensure higher enrichment factor, resulting in enhancement of the method sensitivity. Based on literature data, it can be concluded that halogenated extraction solvents, despite their drawbacks, are still the ones most frequently used for the extraction of various analytes [2,17,22,23,25,26,[35][36][37][38][39]. DLLME has become a powerful tool for sample pretreatment due to its simplicity, rapidity (about 4-6 min), effectiveness and low cost.…”
Section: Introductionmentioning
confidence: 99%
“…The main advantages of DLLME are simplicity, low cost, low reagent consumption, high enrichment factors and agreement with green analytical chemistry. 29,30 It should be highlighted that DLLME may be used in combination with different detection techniques, such as ultraviolet-visible spectrophotometry (UV-Vis), 31,32 flame atomic absorption spectrometry (FAAS), 33 ICP-OES, 34 and ICP-MS. 35 In this study, a DLLME method was developed for the extraction and preconcentration of toxic elements (As and Cd) in sugar for subsequent determination by ICP-MS. Some important parameters of the DLLME method, such as type and volume of extraction and dispersive solvent, pH of sample solution, chelating agent, sample mass and number of washing steps, were studied.…”
Section: Introductionmentioning
confidence: 99%
“…8 A microextração líquido-líquido dispersiva (DLLMEDispersive Liquid-Liquid Microextraction) tem sido proposta como uma alternativa a estes métodos devido à sua simplicidade, baixo custo, baixos limites de detecção e curto tempo de extração. 9 Mais recentemente, também tem sido destacada a eficácia da microextração líquido-líquido com dispersão assistida por agitação em vortex e ultrassom (USVADLLME -ultrasound vortex assisted dispersive liquid-liquid microextraction) na determinação de diversos analitos em matrizes aquosas, como refrigerantes e bebidas alcoólicas por cromatografia em fase gasosa. 10,11 A agitação em vortex e a radiação ultrassônica intensificam o processo de dispersão do solvente extrator e contribuem para aumentar a superfície de contato entre a fase orgânica (solvente extrator) e a fase aquosa, o que favorece a partição dos compostos de interesse entre as duas fases imiscíveis.…”
Section: Introductionunclassified